Pengaruh Packaging dan Kualitas Produk terhadap Keputusan Pembelian : Survei pada Konsumen Produk Sale Ambon Ibu Ooh Cipatujah Kabupaten Tasikmalaya - Reza Nurfauzi; Cece Rakhmat; Ari Arisman (CV. Ulil Albab Corp, 2022)
The objectives of this study was to determine and analyze packaging, product quality and purchasing decisions on Sale Ambon products by Mrs. Ooh Cipatujah Tasikmalaya and the effect of packaging and product quality on purchasing decisions on Sale Ambon products by Mrs. Ooh Cipatujah Tasikmalaya. The research method used in this study is a survey method, while the types of data used in this study are primary data and secondary data. The object of this research is the consumer of Sale Ambon Products, Mrs. Ooh Cipatujah Tasikmalaya, with a sampling technique using simple random sampling method, where the survey was conducted to consumers of Sale products Ambon Mrs. Ooh Cipatujah Tasikmalaya. The data analysis technique used is multiple regression analysis. The results of this test prove that the packaging and product quality simultaneously have a significant effect on purchasing decisions on Sale Ambon products, Mrs. Ooh Cipatujah Tasikmalaya. Likewise, partially packaging and product quality have a significant effect on purchasing decisions on Sale Ambon products, Mrs. Ooh Cipatujah Tasikmalaya.